HUBUNGAN IMBALAN DAN SUPERVISI DALAM PELAKSANAAN PROSES KEPERAWATAN - Masri, Masri; Mukhlis, Mukhlis; Abqariah, Abqariah; Atikah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This study aims to determine the factors related to implementing the nursing process at the Pidie District General Hospital. This type of research is quantitative research with a cross- sectional study design. The results showed a relationship between the reward (p = 0.000) and supervision (p = 0.000). In conclusion, the competence possessed by nurses simultaneously influences the process of nursing care, and the motivation owned influences nurses in carrying out nursing care.Keywords: Reward, Supervision, Nursing Process